Effect of Service Quality and Price on Customer Satisfaction at Kartika Candra in Jakarta - Raden Roro Ayumetarini (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study aims to determine the effect of service quality and price on customer satisfaction at Kartika Candra in Jakarta. The method used was explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study the quality of service significantly influence customer satisfaction by 40.6%, hypothesis testing obtained significance 0,000 <0.05. Price significantly influence customer satisfaction by 40.0%, the hypothesis test obtained significance of 0,000 <0.05. Service quality and price simultaneously have a significant effect on customer satisfaction by 50.3%, hypothesis testing obtained significance 0,000 <0.05.